Po drugiej stronie słowa: granice języka, który nie jest granicą świata - Bogusław Jasiński (Warszawskie Studia Teologiczne)
The presented text examines the limits and possibilities of the linguistic expression of the Inexpressible Being, i.e. Transcendence. The understanding of words, especially poetic ones, but also of all artistic forms, is conditioned by a specific system of language in which not only syntagmatic-declension relations are defined but also those that constitute the semantics itself. Meanwhile, on the example of Homeric poetry and the songs of Psalm 29, we examine how the word can be at the service of being. The author proves that such use of words not only disentangles them from the traditionally understood communication function but above all refers to the old oral traditions. He points to research on the origin of poetry in pre-literate cultures, where oral transmission was primary, and the poetic record was secondary - because it served only as a way of remembering the text and thus served a mnemonic function.